(n+1)! / (n-2)! thx 4 all the ppls that come in and read my post ^^
Follow Math Help Forum on Facebook and Google+
Originally Posted by cwlcwl1212 (n+1)! / (n-2)! thx 4 all the ppls that come in and read my post ^^ Hint:
i understand that (n+1)! = (n+1) x (n+1-1) but i don't understand how can i extract (n-2)! to the equation i need...
n! = n * (n-1) * (n-2)!
Originally Posted by cwlcwl1212 i understand that (n+1)! = (n+1) x (n+1-1) Well, there's your problem, then, because what you "understand" is wrong. What is true is that (n+1)!= (n+1)(n+1-1)(n+1- 2)... (3)(2)(1)= (n+1)(n)(n-1)(n-2)...(3)(2)(1). but i don't understand how can i extract (n-2)! to the equation i need...
View Tag Cloud